Beyond the black box the forensics of airplane crashes - Bibel, George D. (Johns Hopkins University Press, 2008)
"The black box is orange - and there are actually two of them. They house the cockpit recorder and the flight data recorder, instruments vital airplane crash analyses." "But accident investigators cannot rely on the black boxes alone. Beginning with the 1931 Fokker F-10A crash that killed legendary football coach Knute Rockne, this book provides a behind-the-scenes look at plane wreck investigations. Professor George Bibel shows how forensic experts, scientists, and engineers analyze factors like impact, debris, loading, fire patterns, metallurgy, fracture, crash testing, and human tolerances to determine why planes fall from the sky - and how the information gleaned from accident reconstruction is incorporated into aircraft design and operation to keep commercial aviation as safe as possible."